MethyLight TaqMan® assay for quantification of DNA methylation of Reelin (RELN) gene in schizophrenia: preliminary data - Rahim, Mohd Nabil Fikri; Abdul Rahim, Nour El Huda; Mohd. Noor, Hanisah; Abdullah, Nor Zamzila; A.Talib, Norlelawati (2015)
Introduction: Epigenetic changes, particularly DNA methylation are an important mechanism in the regulation of gene expression. Since DNA methylation occurs without genetic sequence alteration, it offers a new insight on the pathogenesis of various complex diseases like cancer and psychiatric disorder such as schizophrenia. Reelin (RELN) gene encodes an extracellular matrix protein that is responsible for neuronal migration during brain development. The methylation study of RELN is needed to clarify its association in schizophrenia. Materials and Methods: DNA samples were extracted from blood of patients diagnosed with schizophrenia in Hospital Tengku Ampuan Afzan, Pahang. The DNA samples were subjected to bisulfite conversion to enhance the methylation areas. Primers and probe were designed to cover CpG rich sites of RELN gene whilst ALU sequences were used as reference target. Sensitivity and specificity of the MethyLight TaqMan® assay were determined by running the assay in serial dilution for the distinction of methylated and unmethylated DNA. With the optimised assay, the DNA methylation of 10 schizophrenia patient samples was measured. Results: This study showed a decreasing detection of methylated alleles in each subsequent dilution using universal human methylated DNA with the Cq value for RELN gene increased from 16.89 to 29.68. We detected the percentage methylation ratio, which valued above zero for the RELN gene in all ten patients ranging from 0.91 to 1.17. Discussion: Our preliminary data suggests the presence of DNA methylation of RELN gene in schizophrenia patients.